The Effect Of Digital Transformation On The Performance Of Msmes In The Economic Era 5.0 - Adelia marta viani; Abi Surya Wijaya (Journal of Management Economic and Financial, 2026)
This study aims to analyze the influence of digital transformation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the Economy 5.0 era, as well as examine the mediating role of digital literacy in this relationship. Economics 5.0 marks a paradigm shift from technology-based automation to the integration of human intelligence and artificial intelligence centered on human values. In this context, MSMEs are required to transform digitally to increase business competitiveness and sustainability. The study used a quantitative approach with a cross-sectional survey design. The research population is all MSME actors registered at the Indramayu Regency Cooperatives and SMEs Office which totals 4,872 units. The sample was determined as many as 360 respondents using stratified random sampling technique. The research instrument is in the form of a questionnaire with a 5-point Likert scale that has gone through validity and reliability tests. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. The results showed that digital transformation had a positive and significant effect on the performance of MSMEs (B= 0.487; p < 0.001). Digital literacy has been shown to partially mediate the relationship between digital transformation and MSME performance (indirect effect = 0.163; LLCI = 0.089; ULCI = 0.251). In addition, there is a positive moderation effect of human resource capabilities in strengthening the relationship between digital transformation and MSME performance. The findings of the research make a theoretical contribution to the development of Resource-Based View (RBV) in the digital context and practical implications for policymakers to design programs to increase MSME digital literacy that are integrated with the Economy 5.0 ecosystem.